Strategies and critical success factors for integrated management systems implementation - Mohammad, Musli; Osman, Mohd Rasid; Mohd Yusuff, Rosnah; Ismail, Napsiah (2005)
This paper discusses the strategies and factors that are critical for IMS implementation. The IMS strategies cover the possible ways and approaches for management systems integration. There are two ways of integrating the management systems which are consecutive implementation of management systems followed by integration and integrate the management systems simultaneously from the beginning. Several approaches that can be applied as a basis for integrating the management systems are include the standard approach, systems approach, Total Quality approach, and Plan-Do-Check-Act (PDCA) approach. Meanwhile, the critical success factors for IMS implementation can be categorized as management commitment and leadership, resources management, focus on stakeholders, education and training, performance measurement, systems and processes, and continual improvement.